Geometria Analítica no Espaço: análise das organizações matemática e didática em materiais didáticos - Costa, Acylena Coelho (2015)
This research aims to analyze how the authors of textbooks organized the activities proposed in relation to the study of Line and Planning for the teaching of Analytic Geometry in Space. Analyses of textbooks substantiate mainly on Anthropological Theory of the Didactic (TAD), with regard to praxeologias proposed by Chevallard (1999) and in didactic variables for the teaching of Analytic Geometry in Space established by Lebeau (2009). Based on the theoretical framework adopted we conducted a qualitative investigation of documentary type, based on a literature review on four textbooks Analytic Geometry devoted to higher education. The methodology used in our research was supported in manual analysis methodology developed by Chaachoua (2014a) analyzing the textbooks the following: time of writing, representation, structure, ecological analysis and praxeological analysis. For regards the praxeological analysis identified six types present in the analyzed manual tasks, namely to: determine the equation of the line in space, determining the straight condition of parallelism in space, to determine the alignment condition of points in space, present plane equation in space as a property of orthogonality, determine a plan characterized by two intersecting lines and characterize algebraically the parallelogram. Among the findings it can be inferred that the authors favor an algebraic modeling of mathematical objects, as well as the techniques adopted by them are situated in the field of Linear Algebra and Analytic Geometry